A, B - evenimente independente

A, B - evenimente dependente

P(AUB)=P(A)+P(B)

P(AUB)=P(A)+P(B) - P(A∩B)

P(A∩B)=P(A)P(B)

P(A∩B)=P(A)P(B/A)

E(X) =

n

∑pi x i

V(X) = E(X2) - [E(X)]2

i =1

s2
Δp$ = z α/2 x
n

$ − $ p≤ p≤ $Δp)
P(pΔp
+ $ 1= α−

$ − p)
$
s 2x = p(1
k

µ - ΔX
µ ≤X ≤ X
µ + ΔX)
µ =1-α
P(X

t calc =

z calc =

µ
X -a
sx
n

k

s 2x =

µ
R

i

s 2x =

- ¶X) 2 ×n i

s x = sx2

i=1

n-1

$ − p)
$
s 2x = p(1

∑ ( yµ -Y )
i=1
T

∑ ( y -Y )

s x = sx2

2

µ 2Y/X T - p
R
Fcalc =
×
µ 2Y/X p - 1
1-R

i

=

∑ (X

µp - a
sx
n
T

2
Y/X

µ =t
ΔX
n-1,α/2

s 2x
n

2

i

R2Y/X

i=1

∑(
T

) ∑(
2

y t -Y =

t=1

t calc =

b$
σ$b$

P b$ − tσtab ×$ b$ b≤

t calc =

a$
σ$a$

P a$− tσtab ×$ a$ a≤

T

t=1

) ∑ ( y -yˆ )

yˆ t -Y +

T

t

t=1

(

b≤+ $t

σtab ×$ b$ 1 = α −

)

(

a≤+ $t

σtab ×$ a$ 1 =α −

)

t

∑ (X

i

- ¶X) 2 ×n i

i=1

n-1

Sign up to vote on this title
UsefulNot useful